A centrifugal microfluidic chip for point-of-care testing of staphylococcal enterotoxin B in complex matrices. Issue 4 (12th January 2022) - Tian, Li Li; Li, Chun Hong; Ye, Qi Chao; Li, Yuan Fang; Huang, Cheng Zhi; Zhan, Lei; Wang, Dong Mei; Zhen, Shu Jun
Abstract : In this study, we utilized a centrifugal microchip platform to develop a microfluidic sensor for Staphylococcal Enterotoxin B (SEB) detection in complex matrices. Abstract : Staphylococcal enterotoxin B (SEB) is a typical biological toxin that causes food poisoning. Currently reported SEB detection methods have the drawbacks of sophisticated sample preparation and being time-consuming and labor-intensive. Herein, we propose a strategy based on an immune sandwich structure operating on a centrifugal microfluidic chip for point-of-care testing (POCT) of SEB. The fluorescent microparticle-labeled primary antibody (CM-EUs-Ab1 ), capture antibody (CAb), and goat anti-mouse IgG antibody (SAb) were modified on the bond area, T-area, and C-area, respectively. When SEB was added, it first reacted with the CM-EUs-Ab1 through the specific recognition between SEB and the Ab1 . Then, under capillarity, the conjugates of SEB and the CM-EUs-Ab1 were captured by the CAb when they flowed to the T-area, and the remaining CM-EUs-Ab1 bound with the SAb in the C-area. Finally, this chip was put into a dry fluorescence detection analyzer for centrifugation and on-site detection of SEB. The fluorescence intensity ratio of the T-area to the C-area was positively correlated with the concentration of SEB. The resulting linear range was 0.1–250 ng mL −1, and the limit of detection (3 σ / k ) was 68 pg mL −1 . This POCT platform only needs 20 μL of sample and can realize the full process of detection within 12 min. This chip also exhibits good stability for 35 days. Additionally, the proposed method has been successfully utilized for the detection of SEB in urine, milk, and juice without any pre-treatment of the samples. Thus, this platform is expected to be applied to food safety testing and clinical diagnosis.